2015
DOI: 10.1155/2015/876805
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effects of Voluntary Exercise in a Rat Model: Role of Matrix Metalloproteinase-2

Abstract: Background. Regular exercise at moderate intensity reduces cardiovascular risks. Matrix metalloproteinases (MMPs) play a major role in cardiac remodeling, facilitating physiological adaptation to exercise. The aim of this study was to examine the influence of voluntary physical exercise on the MMP-2 enzyme activity and to investigate the cardiac performance by measurement of angina susceptibility of the heart, the basal blood pressure, the surviving aorta ring contraction, and the cardiac infarct size after I/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 52 publications
0
21
0
3
Order By: Relevance
“…Notably, another possible explanation is that exercise increased overall cardiovascular and muscular fitness or reduced adipose tissue, rendering exercise dams more adept than sedentary dams in active coping behavior in FST2. Although these factors have not been explicitly studied in forced swim test, voluntary running in rats is beneficial for cardiovascular and skeletal muscle health (Pósa et al, 2015;Mobley et al, 2017) which may ultimately contribute to forced swim test performance. However, using body mass as a covariate still resulted in the main effect of exercise to reduce immobility in the FLX.…”
Section: Maternal Exercise Reduced Depressive-like Behaviour Whereas mentioning
confidence: 99%
“…Notably, another possible explanation is that exercise increased overall cardiovascular and muscular fitness or reduced adipose tissue, rendering exercise dams more adept than sedentary dams in active coping behavior in FST2. Although these factors have not been explicitly studied in forced swim test, voluntary running in rats is beneficial for cardiovascular and skeletal muscle health (Pósa et al, 2015;Mobley et al, 2017) which may ultimately contribute to forced swim test performance. However, using body mass as a covariate still resulted in the main effect of exercise to reduce immobility in the FLX.…”
Section: Maternal Exercise Reduced Depressive-like Behaviour Whereas mentioning
confidence: 99%
“…One limitation of this study is that control Wistar rats were not used. We previously demonstrated that 6 weeks of exercise reduces the myocardial infarct size and improves the angina susceptibility of the heart in Wistar rats [ 8 ]. In the current investigation, we focused on the mechanisms in T2DM GK rats.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the anti-inflammatory role of exercise through (i) down-regulation of proinflammatory mediator gene expression, (ii) induction of anti-inflammatory mediators, and (iii) modulation of HO and NOS enzyme activity. A further therapeutic role of exercise has been found in manifestation of cardiovascular integrity: matrix metalloproteinases were shown to exert major influence in cardiac remodeling through the facilitation of physiological adaptation to exercise [49]. Certainly, the context/environment features (see below) under which exercise is engaged upon may be influential.…”
Section: Health-promotion Through Exercisementioning
confidence: 99%